Analisis ketimpangan pendapatan di negara middle income dan high income: Pendidikan, pengangguran, upah, dan inflasi - Mohammad Rofiuddin (Nur Science Institute, 2024)
Inequality between countries has created other issues that closely correlate with a country's economic conditions. Inequality tends to have a clustered pattern in middle-income and high-income countries. This study aims to analyze the impact of education spending, the role of wages, the relationship between inflation, and the impact of unemployment on income inequality in middle- and high-income countries. The data analysis technique in this study uses multiple linear regression. The study results show that the factors influencing income inequality are unemployment and wages. At the same time, education spending and inflation do not impact changes in income inequality.